2017
DOI: 10.1111/jpi.12424
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin influences the sonic hedgehog signaling pathway in porcine cumulus oocyte complexes

Abstract: Melatonin, which is synthesized in the pineal gland and peripheral reproductive organs, has antioxidant properties and regulates physiological processes. It is well known that melatonin affects in vitro maturation (IVM) of oocytes and embryonic development in many species. However, beneficial effects of melatonin on IVM have been explained mainly by indirect antioxidant effects and little information is available on the underlying mechanism by which melatonin directly acts on porcine cumulus oocyte complexes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 56 publications
(75 reference statements)
6
35
0
Order By: Relevance
“…Regarding the effects of melatonin with or without selective MT2 antagonists (luzindole or 4-P-PDOT) on nuclear maturation of porcine oocytes, no significant difference was observed in immature, degenerate, and MII oocyte rates between any treatment group and the control. The absence of any effects on nuclear maturation by melatonin is consistent with a previous study [ 24 ]. Also, neither of the MT2 antagonists, luzindole or 4-P-PDOT, affected nuclear maturation of porcine oocytes.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding the effects of melatonin with or without selective MT2 antagonists (luzindole or 4-P-PDOT) on nuclear maturation of porcine oocytes, no significant difference was observed in immature, degenerate, and MII oocyte rates between any treatment group and the control. The absence of any effects on nuclear maturation by melatonin is consistent with a previous study [ 24 ]. Also, neither of the MT2 antagonists, luzindole or 4-P-PDOT, affected nuclear maturation of porcine oocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Expansion of the granulosa and cumulus cell layers plays an important role in oocyte maturation [ 26 ], and facilitates ovulation in the ovulatory follicle [ 20 ]. Recently, we demonstrated that the mRNA of melatonin receptors MT1 and MT2 are expressed in porcine cumulus cells [ 24 ]. The presence of melatonin membrane receptors in cumulus cells and the evidence of MT2 receptor-mediated modulation in porcine granulosa cell functions [ 27 ] infers that the MT2 receptor could mediate the effects of melatonin on cumulus expansion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because melatonin reduces ROS and oxidative stress via its direct antioxidative functions, it improves cellular integrity ( Figure 3). However, indirect effects of melatonin via membrane receptors (MT1, MT2) and/or nuclear receptors (RORα) are also important to understand the processes by which melatonin alters the level of oxidative stress [56,57]. Figure 3 summarizes the mechanism of melatonin that are assumed to improve oocyte maturation and quality based on reports to date.…”
Section: Oocyte Maturation Embryo Development and Melatoninmentioning
confidence: 99%